Fura-2 measurements of cultured rat Purkinje neurons show dendritic localization of Ca2+ influx - Hockberger, PE (J Neurosci, 1989)
The specific objectives of this study were the following: (1) to characterize the types of calcium currents in cultured PCs using whole- cell voltage-clamp techniques; (2) using fura-2 imaging techniques, to monitor intracellular Ca2+ levels during application of high potassium, glutamate, or glutamate analogs; and (3) to evaluate the types of calcium channels contributing to the calcium fluxes using pharmacological blocking agents. Voltage-clamp analysis of calcium currents proved to be difficult due to space-clamping problems. The latter was presumably due to the unfavorable geometry of cultured PCs. Nevertheless, we found no evidence for inward currents in cells bathed in TTX-TEA-BaCl2 saline. On the other hand, fura-2 measurements demonstrated that free Ca2+ levels were elevated in PCs following local application of either high-potassium saline or glutamate. When individual cells were injected with fura-2 and analyzed in TTX- containing saline, the Ca2+ elevation was usually greater in the dendrites. Since Ca2+ levels were not elevated in all dendrites of the same cell, the smaller responses in the soma wre not simply due to volumetric differences. Together with the voltage-clamp results, the fura-2 data indicate that calcium channels were localized to certain dendrites. Using selective calcium channel blockers, we found evidence for 2 types of calcium conductances in the dendrites of cultured PCs. The Ca conductance induced by high potassium was reduced in a dose- dependent manner by nifedipine (ED50 = 5 X 10(-7) M), indicating that a high-threshold voltage-dependent calcium channel was present. The Ca response to glutamate (or NMDA) was reduced by 2-amino-5- phosphonovaleric acid (ED50 = 10(-4) M), as well as by nifedipine or 10(-4) M LaCl3, indicating that both voltage-dependent and glutamate- coupled channels were opened by glutamate application.